2017
DOI: 10.4081/dr.2017.6976
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib-associated skin toxicity: a case of maculopapular rash in a 79-year old Caucasian male patient with relapsed Waldenstrom’s macroglobulinemia and review of the literature

Abstract: Waldenstrom's macroglobulinamia (WM) is a rare malignant lymphoproliferative disorder, characterized by monoclonal IgM paraproteinemia and neoplastic proliferation of malignant lymphoplasmacytoid cells in the bone marrow. Traditionally, WM has been treated with modalities similar to those used in the management of other indolent lymphomas. Just recently, based on impressive clinical trial results in heavily pretreated WM patients, a new Bruton Tyrosine Kinase-inhibitor, Ibrutinib, has been approved for the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…By inhibiting EGFR, on the other hand, it displays proinflammatory properties, particularly on the skin, resulting in cutaneous eruptions. 12 Skin rashes are a common AE of the drug, although spongiotic dermatitis and skin rash with intramedullary fibrosis and severe arthralgia is unique to our experience. An increased incidence of skin rash with WM is not evident yet.…”
Section: Discussionmentioning
confidence: 87%
“…By inhibiting EGFR, on the other hand, it displays proinflammatory properties, particularly on the skin, resulting in cutaneous eruptions. 12 Skin rashes are a common AE of the drug, although spongiotic dermatitis and skin rash with intramedullary fibrosis and severe arthralgia is unique to our experience. An increased incidence of skin rash with WM is not evident yet.…”
Section: Discussionmentioning
confidence: 87%
“…In Phase III clinical trials of ibrutinib in CLL, any grade rash was reported in 8% of patients in the RESONATE study and grade ≥3 rash was reported in 3% of patients in RESONATE‐2 (Byrd et al , ; Burger et al , ). While most of the current understanding of ibrutinib‐associated rash comes from individual case reports (Mannis et al , ; Jensen et al , ), reports of larger patient groups being assessed for clinicopathological features, treatment methods and outcomes are starting to emerge (Iberri et al , ). It is the authors' experience that most patients who develop rash have prior history of hypersensitivity to other agents.…”
Section: Resultsmentioning
confidence: 99%
“…One suggested mechanism of ibrutinib-induced drug eruption is through epidermal growth factor receptor (EGFR) inhibition. 9 Although ibrutinib is highly selective for Bruton tyrosine kinase, it exerts off-target effects on other kinases, such EGFR. 10 EGFR inhibitors have well-established cutaneous side effects.…”
Section: Discussionmentioning
confidence: 99%